After-effects of hyperkinetic disorder (HKD) in prospective longitudinal (12 years) study - Kądziela-Olech, Halina (Advances in Psychiatry and Neurology/Postępy Psychiatrii i Neurologii, 2017)
Purpose : Despite the significant increase in the understanding of the hyperkinetic disorder (HKD), our knowledge of the factors associated with the persistence of the disorder and further development of psychopathology is insufficient. The long-term prospective studies have aimed at identifying factors that may determine the adverse course of HKD. Methods : The study group 54 patients (95.1% male) with HKD (mean age 8.1, SD ± 1.7 years at the baseline assessment) was covered by a 12-year observation (mean age of participants: 19.1 ± 1.7 years at the end of the study). Subjects were comprehensively assessed with structured diagnostic interviews and assessments of cognitive functions, including the school and family functioning, the treatment as well as internalizing and externalizing problems. Results : Statistical analysis of the severity of HKD indicated significant reduction in the symptoms after 12 years. The birth complications (OR = 11.187; p = 0.045), chronic conflicts in family (OR = 0.129; p = 0.018) and depression of mother (OR = 6.033; p = 0.045) have proved to be significant risk factors for externalizing disorders in the study group. The single-parent family (OR = 0.099; p = 0.009) and coexistence of mothers’ anxiety disorders (OR = 0.318; p = 0.043) were a significant predictors for the model of internalizing disorders. Only 28 (51.9%) of children used regular systematic therapy. Lack of the systematic treatment was a significant risk factor of transition of HKD to antisocial phenotypes (univariate regression model: R = 0.56; SE = 0.12; p < 0.001). Conclusions : Long-term clinical observation showed that the appropriate systematic treatment until adulthood may significantly reduce undesirable behaviours. Completion of the treatment programme should be monitored systematically for many years, which greatly influences the results of school education and increases the chances for correct psychosocial development. Parents’ mental disorders/conflicts considerably decrease in the treatment effects, thereby increasing the risk of social maladjustment in patients with HKD.